(untitled) (Development Engineering Conferences Center Articles Database, 2025)
The attached narrative review article systematically examines CanSat communication technologies, with a focus on comparing two predominant radio modules: LoRa (long-range) and nRF (short-range). The review highlights the educational and practical significance of CanSats as miniature functional satellites used for STEM education, aerospace research, and environmental monitoring. Key themes include the historical evolution of CanSat projects, foundational communication theory principles such as the Shannon-Hartley theorem and link-budget analysis, and a detailed technical comparison of LoRa and nRF modules. LoRa offers superior long-range communication capabilities with very low power consumption, making it suitable for extended-range telemetry missions, while nRF provides higher data throughput for short-range, real-time control applications. The review integrates empirical findings from recent studies and competition case analyses to illustrate current use cases, challenges, and innovations, including adaptive hybrid communication systems. It concludes by emphasizing the need for future research on dynamic communication architectures that balance range, data rate, and power efficiency, which will enhance the reliability and educational value of CanSat missions. This article serves as a comprehensive guide for educators, students, and practitioners in selecting and optimizing communication technologies for miniature satellite systems.